I survived : the sinking of the Titanic, 1912 - Ball, Georgia; Tarshis, Lauren (Tarshis, Lauren. I survived., 2020)
"Ten-year-old George Calder can't wait to explore every inch of the Titanic, even if his little sister, Phoebe, has to tag along. But when George sneaks away without her and ventures into the first class baggage room, a terrible boom shakes the entire boat. Suddenly, water is everywhere, and George's life changes forever"--Provided by publisher.